In situ hybridization for the detection of rust fungi in paraffin embedded plant tissue sections. Issue 1 (December 2016) - Ellison, Mitchell; McMahon, Michael; Bonde, Morris; Palmer, Cristi; Luster, Douglas
Abstract Background Rust fungi are obligate pathogens with multiple life stages often including different spore types and multiple plant hosts. While individual rust pathogens are often associated with specific plants, a wide range of plant species are infected with rust fungi. To study the interactions between these important pathogenic fungi and their host plants, one must be able to differentiate fungal tissue from plant tissue. This can be accomplished using the In situ hybridization (ISH) protocol described here. Results To validate reproducibility using the ISH protocol, samples ofChrysanthemum  × morifolium infected withPuccinia horiana, Gladiolus  × hortulanus infected withUromyces transversalis andGlycine max infected withPhakopsora pachyrhizi were tested alongside uninfected leaf tissue samples. The results of these tests show that this technique clearly distinguishes between rust pathogens and their respective host plant tissues. Conclusions This ISH protocol is applicable to rust fungi and potentially other plant pathogenic fungi as well. It has been shown here that this protocol can be applied to pathogens from different genera of rust fungi with no background staining of plant tissue. We encourage the use of this protocol for the study of plant pathogenic fungi in paraffin embedded sections of host plant tissue.